Roseomonas vastitatis sp. nov. isolated from Badain Jaran desert in China. Issue 2 (20th December 2019) - Zhao, Li-Li; Deng, Yang; Sun, Ye; Liu, Hong-Yu; Yu, Li-Yan; Zhang, Yu-Qin
Abstract : A Gram-stain-negative, non-motile, coccobacillus-shaped bacterium, designated CPCC 101021 T, was isolated from a sandy soil sample collected from Badain Jaran desert, China. Its 16S rRNA gene sequence was closely related to those of members of the genus Roseomonas, showing high similarities with Roseomonas hibiscisoli THG-N2.22 T (98.0 %), Roseomonas oryzae KCTC 42542 T (97.9 %), Roseomonas rhizosphaerae YW11 T (97.9 %) and Roseomonas suffusca S1 T (97.8 %). In the phylogenetic tree based on 16S rRNA gene sequences, strain CPCC 101021 T formed a distinct subclade with R. oryzae KCTC 42542 T within the genus Roseomonas . Growth of the isolate occurred at 15–37 °C and pH 6.0–8.5, with optimal growth at 30 °C and pH 7.0. The major cellular fatty acids were C18 : 1 ω 7c, summed feature 8 (C16 : 1 ω 7 c/C16 : 1 ω 6c ), summed feature 3 (C16 : 1 ω 6 c/C16 : 1 ω 7c ) and C16 : 0 ω 6c . Q-10 was detected as the main component in the respiratory quinone system, with Q-9 as a minor component. Diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, phosphatidylethanolamine, an unidentified phospholipid, an unidentified aminolipid and an unidentified glycolipid were found in the polar lipid profile. The genomic DNA G+C content was 68.7 mol%. The average nucleotide identity was 84.6 % when comparing the draft genome sequences of strain CPCC 101021 T with R. oryzae KCTC 42542 T . On the basis of genotypic, chemotaxonomic and phenotypic characteristics, strain CPCC 101021 T is proposed to represent a novel species of the genus Roseomonas with the name Roseomonas vastitatis sp. nov. Strain CPCC 101021 T (=J1A743 T =KCTC 62043 T ) is the type strain of the species.